Public Participatory Determination of Sexual Violence Alleviation in Indonesian Universities - Triguswinri, Krisnaldo; Tiorivaldi, Tiorivaldi (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research addresses the serious problem of sexual violence that occurs in educational settings in Indonesia. This crisis requires collaboration between the community and relevant institutions to overcome this problem. The role of civil society becomes very important in shaping effective regulations because they are directly involved in the process of discussion to handling sexual harassment in higher education. This research uses a qualitative method, which produces descriptive data, arguments, or writings as well as behavioral phenomena that can be observed from the subject. This approach allows observation of social and human problems, both in organizational and individual contexts. This research aims to uncover the root causes of sexual violence in the educational environment, as well as how civil society can play an active role in formulating effective regulations to overcome this problem. Data obtained through in-depth interviews, observations, and document analysis will be used to describe the impact of sexual violence, the perspectives of the individuals involved, as well as the efforts that have been made in addressing this issue. The results of this study are expected to provide deeper insights into the complexity of the problem of sexual violence in Indonesian higher education, as well as provide a basis for designing more effective policies in addressing this problem. Through cooperation between civil society, educational institutions, and the government, it is hoped that a safe educational environment free from sexual violence can be created.